1988
DOI: 10.5271/sjweh.1943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to vinyl chloride. An assessment of the evidence.

Abstract: An assessment of the evidenceby Sir Richard Doll, FRS' DOLL R. Effects of exposure to vinyl chloride: An assessment of the evidence. Scand J Work En viron Health 14 ( 1988) 61-78. This paper reviews the possible effects of vinyl chloride on the mortality of occupationally exposed men and the carcinogenic effects that might be observed in the general population as a result of environmental pollution with vinyl chloride. The results of four studies fulfilling the criteria of providing substantial numbers of obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(22 citation statements)
references
References 23 publications
0
21
1
Order By: Relevance
“…In figure 4, we have summarized the accumulating evidence on an association between lung cancer and vinyl chloride exposure by presenting the results of repeated meta-analyses conducted on the data reported up to each year between 1974 and 2002. Using the SMR available before 1987-1990, as well as the suggestion of a higher risk in some groups with longer durations of exposure and latency, one would have concluded that vinyl chloride workers may be at increased risk of lung cancer (2). Results published subsequently, mainly from the two multicenter studies (14,26), did not confirm these findings.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…In figure 4, we have summarized the accumulating evidence on an association between lung cancer and vinyl chloride exposure by presenting the results of repeated meta-analyses conducted on the data reported up to each year between 1974 and 2002. Using the SMR available before 1987-1990, as well as the suggestion of a higher risk in some groups with longer durations of exposure and latency, one would have concluded that vinyl chloride workers may be at increased risk of lung cancer (2). Results published subsequently, mainly from the two multicenter studies (14,26), did not confirm these findings.…”
Section: Discussioncontrasting
confidence: 40%
“…However, the early results were not confirmed by subsequent investigations, which had greater statistical power and better exposure information. Credible reviews conducted in the 1980s concluded, on the basis of the evidence available at that time, that a causal association was plausible in the case of lung cancer (1,2). These examples speak for the need to confirm reports of small excesses of common cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…la r level (4) renewed the interest in this substance. In addition the ep idemiologic data have recently been updated (5-7) and reevaluated in a review (8).…”
mentioning
confidence: 99%
“…Doll published his own analysis, agreeing that angiosarcoma was associated with vinyl chloride but disputing its links with more common cancers (Doll, 1988). Although he found more cases of brain cancer than expected, he argued this was statistically insignificant (Doll, 1988). However, Doll failed to declare his highly paid consultancy (Doll, 2000) for the Chemical Manufacturer's Association (Sass et al, 2005).…”
Section: Sir Richard Dollmentioning
confidence: 99%